2022
DOI: 10.1002/fsn3.2832
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4@PDA/MIL‐101(Cr) as magnetic solid‐phase extraction sorbent for mycotoxins in licorice prior to ultrahigh‐performance liquid chromatography‐tandem mass spectrometry analysis

Abstract: Magnetic solid‐phase extraction (MSPE) strategy based on the Fe3O4@PDA/MIL‐101(Cr) has been proposed to separate and purify five common mycotoxins in licorice, including aflatoxin B1, aflatoxin G1, sterigmatocystin, zearalenone, and ochratoxin A. Integrating the MSPE and solid–liquid extraction/partitioning, a modified QuEChERS was established to adapt to the complex licorice samples. The Fe3O4@PDA/MIL‐101(Cr) was successfully synthesized and characterized by Fourier transform infrared spectroscopy (FT‐IR), sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…As shown in Table S4, the Fe 3 O 4 @PPy microcomposite had one of the best performances in the determination of multiclass mycotoxins, allowing the preconcentration of 13 mycotoxins and being one of the two methods that allowed the simultaneous determination of more mycotoxins and the only one that allowed the determination of DON, T-2, and HT-2 toxins, in addition to the main aflatoxins and the emerging mycotoxins. Furthermore, sample preparation time (25 min) is comparable or better than extraction times previously reported, which are in the 15 min to 1 h and 10 min range [26][27][28][29][30]. In terms of analysis results, it can be observed that the proposed method showed comparable or higher validation parameters to the previously reported methods for other magnetic adsorbents.…”
Section: Comparison With Previously Reported Methodssupporting
confidence: 57%
See 1 more Smart Citation
“…As shown in Table S4, the Fe 3 O 4 @PPy microcomposite had one of the best performances in the determination of multiclass mycotoxins, allowing the preconcentration of 13 mycotoxins and being one of the two methods that allowed the simultaneous determination of more mycotoxins and the only one that allowed the determination of DON, T-2, and HT-2 toxins, in addition to the main aflatoxins and the emerging mycotoxins. Furthermore, sample preparation time (25 min) is comparable or better than extraction times previously reported, which are in the 15 min to 1 h and 10 min range [26][27][28][29][30]. In terms of analysis results, it can be observed that the proposed method showed comparable or higher validation parameters to the previously reported methods for other magnetic adsorbents.…”
Section: Comparison With Previously Reported Methodssupporting
confidence: 57%
“…So far, different nanomaterials have been used for the determination of specific groups of mycotoxins, including multiwalled carbon nanotubes for AFB 1 and ZEN extraction from wheat flour and for main aflatoxins (AFs) (aflatoxins B 1 , B 2 , G 1 and G 2 ). In addition, other multi-walled carbon nanotubes based materials have also been used for the determination of aflatoxins M 1 (AFM 1 ) and M 1 (AFM 2 ), OTA, ZEN, zearalanone (ZAN), α-zeralanol, β-zeralanol, α-zeralenol and β-zeralenol in liquid milk [26,27], as well as coreshell nanomaterials in the form of covalent or metal-organic frameworks for the analysis of maize (AFs, ochratoxins and ENNs) or liquorice (AFG 1 , AFB 1 , sterigmatocystin, ZEN and OTA) [28,29]. Other magnetic nanoparticles (MNPs) based on ferrite cores with nonporous silica shell have been used for fumonisin B1, ZEN, and OTA preconcentration from vegetable oil [30], or with cellulose shell for ENNs and BEA from paprika samples [31].…”
Section: Introductionmentioning
confidence: 99%
“…So far, m‐SPE represents one of the most exploited SPE techniques in numerous fields [111]. Comparatively speaking, literature about the application of m‐SPE in mycotoxin analysis is much more than that of D‐μ‐SPE, involving magnetized carbon nanoparticles [112–119], functionalized magnetic nanoparticles [120–140], and magnetized nanoporous materials [141–149].…”
Section: Spe Techniques For Mycotoxinsmentioning
confidence: 99%
“…The sorbent's highly stable and selective enrichment performance was assumed to result from the high specificity of the aptamers and the maximized aptamer coverage density provided by MIL‐101@Fe 3 O 4 . Our group fabricated MIL‐101(Cr)‐PDA@Fe 3 O 4 and applied it to isolate and purify AFB 1 , AFG 1 , STER, ZEN, and OTA from licorice [149]. MIL‐101(Cr) was synthesized directly around the PDA‐functionalized Fe 3 O 4 .…”
Section: Spe Sorbents Based On Nanomaterials For Mycotoxinsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: . References [ 16 , 38 , 39 , 40 , 41 , 42 , 43 ] are cited in the supplementary materials. Table S1.…”
mentioning
confidence: 99%